Effect of cryopreservation on germination of seeds and zygotic embryos of Calamus shendurunii an endemic rattan of Western Ghats - Jacob, Joemon; Chitra, C.R.; P. Nair, Greeshma; Anilkumar, C.; William Decruse, S. (Journal of Plantation Crops, 2017)
Calamus shendurunii is an endemic rattan of Western Ghats having restricted distribution and limited population. As a prerequisite to device an appropriate method for ex situ conservation of the species, desiccation and cryopreservation of seeds and zygotic embryo has been studied. Seeds extracted from ripened fruits possessed 35 per cent moisture content and exhibited 97 per cent germination. Desiccation to 28 per cent moisture content reduced the germination to 77 per cent. Desiccation below 14 per cent moisture content caused complete loss of seed germinability. Seeds stored under ambient conditions (28Â±2oC/60% RH) for more than seven days reduced germination to less than 40 per cent. Thus, conventional storage is not effective for their ex situ conservation. As an alternative method, excised zygotic embryos were subjected to desiccation and storage in liquid nitrogen. The embryos tolerated desiccation down to 5 per cent exhibiting 60 to 90 per cent germination upon culture into MS medium. Desiccated embryos subjected to liquid nitrogen exposure showed post freeze recovery and germination (80-90%) equal to that of desiccated control samples. Thus the study proved the extreme recalcitrance of C. shendurunii seeds and embryo cryopreservation as an alternative method of their ex situ conservation in gene banks.